A novel non-enzymatic glucose sensor based on NiFe(NPs)–polyaniline hybrid materials. (May 2021) - Lakhdari, Delloula; Guittoum, Abderrahim; Benbrahim, Nassima; Belgherbi, Ouafia; Berkani, Mohammed; Vasseghian, Yasser; Lakhdari, Nadjem
Abstract: This article was focused on the elaboration of NiFe-Polyaniline glucose sensors via electrochemical technique. Firstly, the PANi (polyaniline) fibers were synthesized by oxidation of the monomer aniline on FTO (fluorine tin oxide) substrate. Secondly, the Nickel–Iron nanoparticles (NiFe (NPs)) were obtained by the Chronoamperometry method on the Polyaniline surface. The NiFe-PANi hybrid electrode was characterized by scanning electron microscopy (SEM), force atomic microscopy (AFM), Fourier-transformed infrared (FTIR), and X-ray diffraction (XRD). The electrochemical glucose sensing performance of the NiFe alloy nanoparticle was studied by cyclic voltammetry and amperometry. The fabricated glucose sensor Ni–Fe hybrid material exhibited many remarkable sensing performances, such as low-response time (4 s), sensitivity (1050 μA mM −1 cm −2 ), broad linear range (from 10 μM −1 mM), and low limit of detection (LOD) (0.5 μM, S/N = 3). The selectivity, reliability, and stability of the NiFe hybrid material for glucose oxidation were also investigated. All the results demonstrated that the NiFe-PANi/FTO hybrid electrode is very promising for application in electrochemical glucose sensing. Graphical abstract: Schematic oxidation of glucose on the NiFe(NPs)-PANi electrode. Image 1 Highlights: Novel non-enzyme electrochemical NiFe-PANi hybrid electrode for glucose detection was synthesized. PANi fibers were synthesized by oxidation of the monomer aniline on FTO. Ni–Fe NPs were obtained by the Chronoamperometry method on the PANi surface. NiFe-PANi showed good selectivity, reliability, and stability for glucose detection.